2021
DOI: 10.1289/ehp8928
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide DNA Methylation and Pesticide Use in the Agricultural Lung Health Study

Abstract: Background: Pesticide exposure is associated with many long-term health outcomes; the potential underlying mechanisms are not well established for most associations. Epigenetic modifications, such as DNA methylation, may contribute. Individual pesticides may be associated with specific DNA methylation patterns but no epigenome-wide association study (EWAS) has evaluated methylation in relation to individual pesticides. Objectives: We conducted an EWAS of DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 65 publications
(146 reference statements)
2
17
0
Order By: Relevance
“… 35 Inflated test statistics (lambda) was corrected using BACON, and p -values were estimated after correction for inflation and bias in the study. Previous studies of epigenome-wide analyses of DNA methylation using BACON package reported lambda varying from 0.79 to 1.40, 36 , 37 which supported the confidence of our study (lambda:1.29). A false discovery rate (FDR) threshold was determined at and delta beta was determined at as the threshold for epigenome-wide testing.…”
Section: Methodssupporting
confidence: 91%
“… 35 Inflated test statistics (lambda) was corrected using BACON, and p -values were estimated after correction for inflation and bias in the study. Previous studies of epigenome-wide analyses of DNA methylation using BACON package reported lambda varying from 0.79 to 1.40, 36 , 37 which supported the confidence of our study (lambda:1.29). A false discovery rate (FDR) threshold was determined at and delta beta was determined at as the threshold for epigenome-wide testing.…”
Section: Methodssupporting
confidence: 91%
“…Such genetic modifications could act as carcinogenic agents. Differentially methylated CpGs have been found to be unique to the active ingredients of marketed pesticides such as mesotrione, dicamba, acetochlor, picloram atrazine, malathion, glyphosate, and metolachlor ( Hoang et al, 2021 ). Occupational and non-occupational pesticide exposure, as well as chronic and high pesticide exposure in human beings, lead to altered genomic methylation.…”
Section: Role Of Pesticides In Genetic Damagementioning
confidence: 99%
“…40 A recent finding of the AHS, in a genome-wide DNA methylation study, found methylation of PAX6 with ATZ; this implicates ATZ exposure in the development of diabetes and abnormal eye development. 41 The United States Geological Survey reported ten or more pesticide contaminants in approximately 20% of their tests and two or more in 90% of their tests in streams. 42 Thus, flora and fauna are consistently exposed to multiple pesticides and, indeed, large quantities of ATZ are lost to the environment.…”
Section: Environmental Significancementioning
confidence: 99%
“…40 A recent finding of the AHS, in a genome-wide DNA methylation study, found methylation of PAX6 with ATZ; this implicates ATZ exposure in the development of diabetes and abnormal eye development. 41…”
Section: Introductionmentioning
confidence: 99%